2015
DOI: 10.1016/j.jpowsour.2015.04.073
|View full text |Cite
|
Sign up to set email alerts
|

Study of acetylene poisoning of Pt cathode on proton exchange membrane fuel cell spatial performance using a segmented cell system

Abstract: Acetylene is a welding fuel and precursor for organic synthesis, which requires considering it to be a possible air pollutant. In this work, the spatial performance of a proton exchange membrane fuel cell exposed to 300 ppm C 2 H 2 and different operating currents was studied with a segmented cell system. The injection of C 2 H 2 resulted in a cell performance decrease and redistribution of segments' currents depending on the operating conditions. Performance loss was 20-50 mV at 0.1-0.2 A cm −2 and was accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 117 publications
5
22
1
Order By: Relevance
“…For naphthalene, the cell voltage transient was interrupted before a steady state was obtained (Figure 1f), which also led to a low-frequency artefact that could not be fitted to the equivalent circuits of Figure 3a-c. The impedance spectra agree with the prior results for acetonitrile [25][26][27][28], acetylene [36][37][38], bromomethane [28][29][30], isopropanol [31], methyl methacrylate [31], naphthalene [40], and propene [28,31,41]. Molecules 2020, 25 and structural modifications to the catalyst layer that are relatively more impactful for the lower catalyst loading.…”
Section: Impedance Spectrasupporting
confidence: 86%
See 1 more Smart Citation
“…For naphthalene, the cell voltage transient was interrupted before a steady state was obtained (Figure 1f), which also led to a low-frequency artefact that could not be fitted to the equivalent circuits of Figure 3a-c. The impedance spectra agree with the prior results for acetonitrile [25][26][27][28], acetylene [36][37][38], bromomethane [28][29][30], isopropanol [31], methyl methacrylate [31], naphthalene [40], and propene [28,31,41]. Molecules 2020, 25 and structural modifications to the catalyst layer that are relatively more impactful for the lower catalyst loading.…”
Section: Impedance Spectrasupporting
confidence: 86%
“…a result, the current density was temporarily lowered and the contaminant injection was interrupted before a steady state was obtained to avoid an automatic test station shutdown. Contamination and recovery transients are qualitatively and quantitatively consistent with the prior results for acetylene [23,[36][37][38][39], bromomethane [23,[28][29][30], isopropanol [23,31], methyl methacrylate [23,31], naphthalene [23,40], and propene [23,28,31,41]. Figure 1b-g illustrates voltage transients for the other contaminants.…”
Section: Cell Voltage Transientssupporting
confidence: 82%
“…Therefore, alkaline earth metal carbonate–alkaline earth MH systems were selected for further detailed study. Moreover, the FTIR spectra featured no absorptions of CO 2 and CO, indicating that no CO x intermediates were produced under these conditions, which is important in view of the fact that carbon monoxide, carbon dioxide, and ammonia easily poison the catalysts of proton exchange membrane fuel cells . To re‐stress, methane was the sole gaseous hydrocarbon product of reactions of alkaline earth metal carbonates with alkaline earth MHs, which suggested that the reactions are highly selective.…”
Section: Resultsmentioning
confidence: 99%
“…It could be shown that air pollutants can increase these inhomogeneities. 26 In order to achieve a better understanding of the degradation mechanisms of the nitrogen compounds current distribution measurements were examined.…”
Section: Methodsmentioning
confidence: 99%